Studi Komparatif Antara Arbitrase Ad Hoc dan Arbitrase Institusional dalam Proses Penunjukan Arbiter dan Dampaknya terhadap Kasus Arbitrase - Muhammad Iqbal Arieza; Ahmad Ahmad (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the comparative characteristics of ad hoc arbitration and institutional arbitration, with particular emphasis on the arbitrator appointment process and its impact on arbitral proceedings and outcomes. The research employs a normative juridical approach supported by comparative analysis of legal frameworks, arbitral practices, and relevant scholarly literature. The findings indicate that the method of appointing arbitrators plays a decisive role in shaping procedural fairness, the legitimacy of arbitral awards, and the effectiveness of their enforcement. Ad hoc arbitration offers substantial flexibility for the parties to determine arbitrators based on mutual agreement, yet this flexibility may generate legal uncertainty when appointment mechanisms are inadequately regulated. In contrast, institutional arbitration provides structured appointment procedures, ethical standards, and administrative oversight, which contribute to stronger legitimacy and higher acceptance of arbitral awards by national courts. The study concludes that institutional arbitration tends to offer greater legal certainty and enforceability, while ad hoc arbitration remains viable when supported by clear contractual arrangements. These distinctions highlight the strategic importance of arbitrator appointment mechanisms in achieving effective dispute resolution through arbitration.